Efektivitas Layanan dan Administrasi dalam Optimalisasi Program Kredit Usaha Rakyat (KUR) untuk Pengembangan Usaha Masyarakat - Muhammad Wahyudin (Genius: Jurnal Ekonomi Dan Manajemen, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in national economic growth, especially in creating jobs and improving people's welfare. To support their sustainability and development, access to financing is a major factor. Bank Rakyat Indonesia (BRI) through the Kredit Usaha Rakyat (KUR) program plays a role in channeling business capital to MSME players to increase their business capacity. This research aims to evaluate the effectiveness of services and administration in optimizing the KUR program, with a focus on its implementation at BTN Blora Branch Office. This research used a descriptive qualitative method, with data collection through direct observation, in-depth interviews, and documentation studies. The research informants consisted of banking staff who handle KUR services, loan recipients, and regulators who oversee business credit policies. The main objective of this study was to analyze how administrative services affect the effectiveness of the KUR program, as well as to identify challenges faced in the implementation of digital banking services. The results show that although BTN's administrative services are well established, there are still challenges in procedural efficiency and digital literacy among customers. The use of digital systems in KUR administration has contributed to the acceleration of services, but the lack of socialization has resulted in a low level of utilization of digital services. Thus, a more effective strategy is needed in optimizing digital administration and mentoring for customers to ensure maximum utilization of KUR in the development of MSMEs.